Studying the genetic basis of masting. (6th December 2021) - Satake, Akiko; Kelly, Dave
Abstract : The mechanisms underlying mast seeding have traditionally been studied by collecting long-term observational data on seed crops and correlating seedfall with environmental variables. Significant progress in ecological genomics will improve our understanding of the evolution of masting by clarifying the genetic basis of masting traits and the role of natural selection in shaping those traits. Here, we summarize three important aspects in studying the evolution of masting at the genetic level: which traits govern masting, whether those traits are genetically regulated, and which taxa show wide variation in these traits. We then introduce recent studies on the molecular mechanisms of masting. Those studies measure seasonal changes in gene expression in natural conditions to quantify how multiple environmental factors combine to regulate floral initiation, which in many masting plant species is the single largest contributor to among-year variation in seed crops. We show that Fagaceae offers exceptional opportunities for evolutionary investigations because of its diversity at both the phenotypic and genetic levels and existing documented genome sequences. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.